A School in Rosignano Solvay (1961-'63) (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2013)
For Ludovico Quaroni, the beginning of the 1960s was a period in which there were great opportunities to design buildings, as well as many challenging subjects and difficult topics that needed to be tackled and that demanded experimentation. The school at Rosignano cannot but seem a minor episode when compared with his work on the urban plan of Ravenna or his early experiences of planning in Syria and Tunisia. Moreover, his objective of winning the high-prestige competition to design the business centre in Turin, or his most valuable work in the Punta Ala district, or, again, his design for the tax office of the Ravenna Savings Bank, all came happily to fruition. The school was a discrete piece, and certainly one of his least known works, but it nevertheless seems to represent well the counterpoint of theme and contents, an eagerly sought alternation between different dimensions and languages, which he seemed always to be seeking by moving from solemn architectural phrases to workaday discoveries, measures and accents. We believe that for these reasons the school is something that should not be forgotten.